2004
DOI: 10.1182/blood-2004-04-1411
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural correlations of individual αIIbβ3 molecules

Abstract: The divalent cation Mn 2؉ and the reducing agent dithiothreitol directly shift integrins from their inactive to their active states. We used transmission electron microscopy and laser tweezers-based force spectroscopy to determine whether structural rearrangements induced by these agents in the integrin ␣IIb␤3 correlate with its ability to bind fibrinogen. Mn 2؉ increased the probability of specific fibrinogen-␣IIb␤3 interactions nearly 20-fold in platelets, and both Mn 2؉ and dithiothreitol increased the prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
69
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 48 publications
10
69
0
Order By: Relevance
“…Unfortunately, as shown above, protein aggregation and particle size heterogeneity were observed, which made it impossible to obtain the configuration of ␣IIb␤3 in solutions with Mn 2ϩ as planned. This observation is in agreement with the earlier chromatographic elution of ␣IIb␤3 in Mn 2ϩ buffer with respect to ␣IIb␤3 in Ca 2ϩ buffer and with previous observations that Mn 2ϩ , but not Ca 2ϩ , can induce formation of dimers and multimers of whole ␣IIb␤3 and r-␣V␤3 (13,33).…”
Section: Reconstruction Of the High Resolution Structural Model Of Whsupporting
confidence: 81%
“…Unfortunately, as shown above, protein aggregation and particle size heterogeneity were observed, which made it impossible to obtain the configuration of ␣IIb␤3 in solutions with Mn 2ϩ as planned. This observation is in agreement with the earlier chromatographic elution of ␣IIb␤3 in Mn 2ϩ buffer with respect to ␣IIb␤3 in Ca 2ϩ buffer and with previous observations that Mn 2ϩ , but not Ca 2ϩ , can induce formation of dimers and multimers of whole ␣IIb␤3 and r-␣V␤3 (13,33).…”
Section: Reconstruction Of the High Resolution Structural Model Of Whsupporting
confidence: 81%
“…Previously, we found that the presence of Mn 2ϩ favored the formation of higher affinity ␣IIb␤3-fibrinogen complexes characterized by a higher binding energy and reduced off-rate (20,21,23). Here, we found that Mn 2ϩ shifts ␣IIb␤3 to a higher activation state by modulating both the on-rate and the rate at which ␣IIb␤3 transitions from a lower to a higher affinity state.…”
Section: Discussionmentioning
confidence: 63%
“…The polypeptide composition, purity, and lack of oligomerization of ␣IIb␤3 and fibrinogen were assessed by SDS-PAGE and by transmission electron microscopy. The binding probability and rupture force profiles ensure single molecule interactions as inferred from the criteria based on previous experiments performed using the same protein binding protocols (12,20,21,23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrin affinity can be uniquely regulated through a process called inside-out signaling, in which stimuli received by other cell surface receptors initiate intracellular signals that impinge on integrin cytoplasmic domains and alter integrin conformation and ligand-binding affinity . In addition, binding of ligand to integrins can trigger the transduction of extracellular signals into the cytoplasm and activate downstream signals in the classic outside-in signaling (Litvinov et al, 2004;Luo et al, 2007). Moreover, lateral assembly of integrins (integrin clustering) is known to augment integrin-mediated adhesion by increasing the bond valency and also contributes to signal transduction (Miyamoto et al, 1995).…”
Section: Introductionmentioning
confidence: 99%